Suicide risk among male substance users in residential treatment: Evaluation of the depression–distress amplification model. (30th March 2016) - Capron, Daniel W.; Bujarski, Sarah J.; Gratz, Kim L.; Anestis, Michael D.; Fairholme, Christopher P.; Tull, Matthew T.
Abstract: Suicide is a leading cause of death and is significantly elevated among those with substance use disorders (SUDs). However, specific mechanisms of suicide in this population have been relatively understudied. The depression–distress amplification model posits that one pathway to increased suicide risk is through the intensification of depressive symptoms by anxiety sensitivity cognitive concerns. However, this model has not been tested in populations with SUDs. The current study tested the depression–distress amplification model of suicide risk and examined the relation of anxiety sensitivity to suicide risk in a sample of men in residential SUD treatment. Consistent with prior work, anxiety sensitivity cognitive concerns were significantly associated with suicide risk. Moreover, and consistent with the depression–distress amplification model, anxiety sensitivity cognitive concerns related to elevated suicide risk among those with a current major depressive episode specifically, above and beyond insomnia (another risk factor for suicide) and relevant covariates. The results of this study corroborate the relevance of anxiety sensitivity cognitive concerns and the depression–distress amplification model to suicide risk in an at-risk clinical sample of SUD patients. Findings suggest the importance of assessing anxiety sensitivity cognitive concerns and targeting this vulnerability through brief interventions to reduce suicide risk. Highlights: Anxiety sensitivity (AS) cognitive concerns associated with suicide risk. AS physical and social concerns were not associated with suicide risk. AS cognitive concerns predict suicide risk among those with current depression. As predicted, Insomnia severity did not interact with depression to predict suicide.